Closed-form correlations of pressure drop and thermal resistance for a plate fin heat sink with uniform air jet impingement. (15th March 2017) - Kim, Tae Hoon; Do, Kyu Hyung; Kim, Sung Jin
Highlights: Correlations for a plate fin heat sink with uniform jet impingement were proposed. The correlations provide the theoretical limits for the performance of the heat sink. The effect of flow uniformity on cooling performance of the heat sink was discussed. The present analysis can be implemented in thermal optimization of the heat sink. Abstract: This paper proposes closed-form correlations of the pressure drop and thermal resistance for a plate fin heat sink with uniform air jet impingement, which will be useful in determining the theoretical limits for its performance under ideal conditions. The correlations are based on the volume averaging technique and validated using the corresponding numerical results. A comparison between the proposed correlations and existing experimental data revealed that the performance results by previous studies were obtained under conditions of non-uniform jet impingement and that flow uniformity at the inlet is one of the major parameters influencing the cooling performance. The contour plot of the thermal resistance ratio showed that uniform flow conditions provide the upper limit for the thermal performance of the plate fin heat sink with jet impingement. Thus, the correlations can be utilized to evaluate how the thermal performance of a heat sink with actual inlet flow conditions deviates from an ideal one. In addition, using the correlations, thermal optimization of the plate fin heat sink with uniform jet impingement was performed. For selected cases, this paper demonstrates that the cooling performance of the heat sink with optimum geometry is approximately 50% better than that of the conventional heat sink.